2010
DOI: 10.1088/0031-9155/55/21/007
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity-based MR elastography of skeletal muscle

Abstract: An in vivo multifrequency magnetic resonance elastography (MRE) protocol was developed for studying the viscoelastic properties of human skeletal muscle in different states of contraction. Low-frequency shear vibrations in the range of 25-62.5 Hz were synchronously induced into the femoral muscles of seven volunteers and measured in a cross-sectional view by encoding the fast-transverse shear wave component parallel to the muscle fibers. The so-called springpot model was used for deriving two viscoelastic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 40 publications
10
122
3
1
Order By: Relevance
“…Other studies using similar techniques include Klatt et al,33 and Barnhill et al,34 who reported values for the storage modulus (i.e., G′ ) in the ranges of 0.7 to 2 kPa, and 1.0 to 1.9 kPa, respectively. These data, however, refer to a single frequency acquisition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies using similar techniques include Klatt et al,33 and Barnhill et al,34 who reported values for the storage modulus (i.e., G′ ) in the ranges of 0.7 to 2 kPa, and 1.0 to 1.9 kPa, respectively. These data, however, refer to a single frequency acquisition.…”
Section: Discussionmentioning
confidence: 92%
“…The actuator was designed at the MRE Research Laboratory, Charité‐Universitätsmedizin Berlin, Germany33 and was firmly secured around the leg using Velcro straps to ensure sufficient wave transmission. A cod liver oil capsule was placed on the actuator to facilitate image plane positioning, which was prescribed 2 cm above the proximal actuator edge to avoid potential effects of compression of the muscle by the actuator ring 45.…”
Section: Methodsmentioning
confidence: 99%
“…This was seen as representative of the circular ring actuator that is often used for inducing vibrations into the leg [22,1]. Frequencies of 25, 37.5, 50 and 62.5 Hz were applied [22,12].…”
Section: Boundary and Loading Conditionsmentioning
confidence: 99%
“…The model parameters for the biceps, gracilis, semitendinosus and semimembranosus muscles were calculated in the aforementioned Chakouch study and have been utilised here. [22] calculated storage and loss modulus values at multiple frequencies for the grouped quadricep muscles (rectus femoris, vastus medialis, vastus intermedius and vastus lateralis). Parameters for the Zener model based on these measurements were calculated by minimising the cost function in the same manner as previous studies [24,23]:…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation